EXTH-98. ENHANCING T CELL TRAFFICKING OF CD3-ENGAGING IMMUNOTHERAPY TO TUMORS OF THE CENTRAL NERVOUS SYSTEM. (14th November 2022) - Singh, Kirit; Foster, Matthew; Hotchkiss, Kelly; Snyder, David; Khasraw, Mustafa; Sampson, John
Abstract: BACKGROUND: Effective immunotherapy against tumors of the central nervous system (CNS) requires that the drug the blood brain barrier (BBB) and encounter immune cells. We have previously described a mechanism which may facilitate transport of CD3-engaging therapeutics into the CNS, via carriage on activated T cells. Building on this, we sought to produce specific T cell phenotypes that rapidly enter and accumulate in the CNS. METHODS: 8–10-week-old C57/Bl6 mice (n=5-6 per group) were implanted with 30, 000 CT2AvIII cells which established over 14 days. Mice received (1) CD45.1 lymphocytes activated with IL-7 and Concanavalin-A (single intravenous (IV) injection, 1 x 10 7 adoptive lymphocyte transfer (ALT)) or (2) CD45.1 lymphocytes activated with IL-2 and serial Con-A stimulation. Mice were sacrificed 3 hours following ALT and their brains analysed via flow cytometry. A follow-up timepoint of 48 hours was also analysed. Groups were compared using a Mann-Whitney U test. RESULTS: Ex vivo culture in group 1 yielded a mixed population of T effector and T central memory cells whereas group 2 resulted in terminally differentiated T effector memory cells only. VLA-4, a migratory integrin involved in T cell entry into the CNS was upregulated in the IL-7 group. Mice in Group 1 demonstrated significantly enhanced entry of CD8+ effector and memory T cells into tumor bearing hemispheres 3- and 48-hours following administration compared to Group 2 (p = 0.005, p = 0.0159 respectively). CONCLUSIONS: Varying the cytokine cocktail used for ex vivo activation and expansion of T cells results in markedly different trafficking properties and phenotype composition. Ongoing work will determine how enhanced T cell localization to tumor affects accumulation of immunotherapy via the hitchhiking mechanism. Further, we will evaluate the safety of combinatorial CD3-engaging immunotherapy and ALT in Phase I trials (NCT04903795) using a cGMP Brain Bi-specific T cell engager (BRiTE).